Comparative detection efficacy of primers targeting SpeI-AvaI restriction fragment and small subunit ribosomal RNA gene of Babesia bigemina - KAUR, PARAMJIT; JUYAL, PRAYAG DUTT; SHARMA, AMRITA; SINGLA, LACHHMAN DAS; MUKHOPADHYAY, CHANDRA SEKHAR (The Indian Journal of Animal Sciences, 2023)
The objective of the study is to evaluate the comparative detection efficacy of primers targeting SpeI-AvaI restriction fragment and small subunit ribosomal RNA (SSU rRNA) gene of Babesia bigemina by employing conventional polymerase chain reaction (PCR) on 783 animals (296 cattle and 487 buffaloes) of low lying (bet) area of Punjab. The detection rate of SpeI-AvaI and SSU rRNA PCR assays was 3.96% (31/783), and 6.64% (52/783), respectively. Among cattle and buffaloes, prevalence of B. bigemina was higher (P